Salmon gill poxvirus disease in Atlantic salmon fry as recognized by improved immunohistochemistry also demonstrates infected cells in non‐respiratory epithelial cells. Issue 7 (10th May 2018) - Gjessing, M C; Christensen, D H; Manji, F; Mohammad, S; Petersen, P E; Saure, B; Skjengen, C; Weli, S C; Dale, O B
Abstract: Gill diseases cause serious losses in farming of Atlantic salmon and the number of agents involved increases. Salmon gill poxvirus (SGPV) and the gill disease in causes where SGPV apparently was the only disease‐causing agent were initially characterized. Recently, it was further shown that SGPV can be a common denominator in widely different multifactorial gill diseases. Here, we present the challenge of diagnosing gill disease with SGPV in salmon fry of 0, 3–5 grams. Apoptosis of gill lamellar epithelial cells and hemophagocytosis was also observed in fry similar to findings in smolts and grow‐out fish. Using our newly developed immunohistochemistry method, we further demonstrate that some of the apoptotic epithelial cells covering the oral cavity were positive for SGPV. Thus, SGPV is not restricted to respiratory epithelium alone and may infect the fish at very early life stages. Furthermore, as the cases examined here are from Norway, Faroe Island and Scotland, we show that SGPV is more widespread than previously reported.